1999
DOI: 10.1111/j.1749-6632.1999.tb09175.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Otolith Pathways to Brainstem and Cerebellum

Abstract: Our knowledge of otolith pathways is developing rapidly, but is still far from complete. Primary afferents from the sacculus and utricle terminate mainly in the lateral, inferior and caudal superior vestibular nuclei, and the ventral cerebellum, in particular the nodulus. Otolith signals descend via reticulo- and vestibulospinal pathways in the spinal cord to influence neck motoneurons and ascending proprioceptive afferents. Utricular information can reach the extraocular eye muscles via mono-, di-, and multis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(103 citation statements)
references
References 85 publications
0
100
1
2
Order By: Relevance
“…A graviceptional role of the mammalian saccule is indicated by the termination of SA afferent fibers in the vestibular nuclei (see Büttner-Ennever 1999), by the presence of SA signals in particular spinal motoneurons that are involved in postural control Uchino et al 1997;Wilson et al 1977) and by the presence of powerful sacculo-collic reflexes Xerri et al 1987). However, in contrast to a contribution of SA signals to postural control, only very few 2°VOR neurons in cat receive afferent SA signals Sato et al 2000); this is compatible with the absence of a disynaptic sacculo-ocular reflex pathway (Isu et al 2000) and a very weak vertical maculo-ocular reflex (e.g., in rat, Hess and Dieringer 1991).…”
Section: Functional Role Of Otolith Organs In Frog and Mammalsmentioning
confidence: 99%
“…A graviceptional role of the mammalian saccule is indicated by the termination of SA afferent fibers in the vestibular nuclei (see Büttner-Ennever 1999), by the presence of SA signals in particular spinal motoneurons that are involved in postural control Uchino et al 1997;Wilson et al 1977) and by the presence of powerful sacculo-collic reflexes Xerri et al 1987). However, in contrast to a contribution of SA signals to postural control, only very few 2°VOR neurons in cat receive afferent SA signals Sato et al 2000); this is compatible with the absence of a disynaptic sacculo-ocular reflex pathway (Isu et al 2000) and a very weak vertical maculo-ocular reflex (e.g., in rat, Hess and Dieringer 1991).…”
Section: Functional Role Of Otolith Organs In Frog and Mammalsmentioning
confidence: 99%
“…The OTR appears in humans with imbalance in the direct utricular-ocular pathways in the brainstem and also in some patients with various cerebellar lesions (eg, nodulus and dentate nucleus). 5,[10][11][12][13][14][15][16][17][18][19][20] Experiments have shown that the utricular-ocular imbalance can often be overridden by altered patterns of otolith stimulation (upright-supine test) affirming the supranuclear origin of the misalignment. 21 The OTR has been attributed to the emergence of a phylogenetically old response, best appreciated in lateral-eyed animals, as in humans it has been largely superseded by mechanisms that are optimized for binocular, foveate, and frontal-eyed vision.…”
Section: Ocular Misalignment With Cerebellar Diseasementioning
confidence: 99%
“…In the present situation, where the LVOR is mediated by a three-neuron arc through vestibular and oculomotor nuclei following afferent input from the otolith organs, central modulation is thought to be achieved primarily by the nodular and uvular divisions of the cerebellum (1,29). The nodulus/uvula exert their influence by means of Purkinje cell inhibition on the vestibular nuclei but the strength of the influence can be modulated by retinal and eye proprioceptive inputs to the cerebellum via the inferior olive.…”
Section: Discussionmentioning
confidence: 92%